1995
DOI: 10.1146/annurev.pc.46.100195.000545
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reactions and Energy Transfer at Very Low Temperatures

Abstract: Experimental studies of gas-phase chemical reactions and molecular energy transfer at very low temperatures and between electrically neutral species are reviewed. Although work of collisionally induced vibrational and rotational transfer is described, emphasis is placed on very recent results on the rates of free radical reactions obtained by applying the pulsed laser photolysis (PLP)-laser-induced fluorescence (LIF) technique in a CRESU (Cinétique de Réactions en Ecoulement Supersonique Uniforme) apparatus at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 38 publications
2
101
0
3
Order By: Relevance
“…[53,58]) in which a large diameter Laval nozzle is used to obtain genuine thermal equilibrium within a supersonic beam at temperatures as low as 7 K, but more typically down to 15 K. Reactive species are generated either by pulsed laser photolysis or photoionization within a helium beam using a high backing pressure and high densities (∼10 16 molecules cm −3 ). Reactive collisions in the jet occur in the 100-500 µs during which the flow remains uniform.…”
Section: Low-temperature Chemistrymentioning
confidence: 99%
“…[53,58]) in which a large diameter Laval nozzle is used to obtain genuine thermal equilibrium within a supersonic beam at temperatures as low as 7 K, but more typically down to 15 K. Reactive species are generated either by pulsed laser photolysis or photoionization within a helium beam using a high backing pressure and high densities (∼10 16 molecules cm −3 ). Reactive collisions in the jet occur in the 100-500 µs during which the flow remains uniform.…”
Section: Low-temperature Chemistrymentioning
confidence: 99%
“…10 Here, one reactant and a precursor to the second one are co-expanded in a uniform expansion through a Laval nozzle. The reaction is induced by the formation of the second reactant by electron bombardment or with a laser.…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory work (Sims & Smith 1995) has shown that certain classes of neutralneutral reactions can occur rapidly at very low temperature, but the extent of this phenomenon is still not determined. In general, the inclusion of rapid neutral-neutral reactions tends to depress the calculated early-time abundances of complex molecules, sometimes catastrophically (Herbst et al 1994).…”
Section: Introductionmentioning
confidence: 99%